A Cactus‐Derived Toxin‐Like Cystine Knot Peptide with Selective Antimicrobial Activity. Issue 7 (27th March 2015) - Aboye, Teshome L.; Strömstedt, Adam A.; Gunasekera, Sunithi; Bruhn, Jan G.; El‐Seedi, Hesham; Rosengren, K. Johan; Göransson, Ulf
Abstract Naturally occurring cystine knot peptides show a wide range of biological activity, and as they have inherent stability they represent potential scaffolds for peptide‐based drug design and biomolecular engineering. Here we report the discovery, sequencing, chemical synthesis, three‐dimensional solution structure determination and bioactivity of the first cystine knot peptide from Cactaceae (cactus) family: Ep‐AMP1 from Echinopsis pachanoi. The structure of Ep‐AMP1 (35 amino acids) conforms to that of the inhibitor cystine knot (or knottin) family but represents a novel diverse sequence; its activity was more than 500 times higher against bacterial than against eukaryotic cells. Rapid bactericidal action and liposome leakage implicate membrane permeabilisation as the mechanism of action. Sequence homology places Ec‐AMP1 in the plant C6‐type of antimicrobial peptides, but the three dimensional structure is highly similar to that of a spider neurotoxin.